CURRENT APPROACHES TO TREATING NON-RHABDOID SOFT TISSUE SARCOMAS OF THE HEAD AND NECK IN CHILDREN: A REVIEW OF LITERATURE - M. V. Bolotin; A. V. Lopatin (Опухоли головы и шеи, 2015)
Soft tissue sarcomas constitute approximately 8–10 % of all malignancies in children and adolescents and half of them are rhabdomyosarcoma. The second half makes up a heterogeneous group of malignancies of mesenchymal non-rhabdoid origin, which have been recently referred to as an individual group of non-rhabdoid soft tissue sarcomas (an adult type) in increasing frequency. The choice of a treatment option depends on a number of factors: its histological structure, location, stage of a tumor; the possible performance of radical surgery; and the grade of tumor differentiation. Surgery is the basic treatment; if it is impossible, chemoradiotherapy is performed at stage 1.